Functional significance of commonly regulated genes in mechanically and chemically induced retinal ganglion cell death in rat eyes - Masaaki Kageyama; Koji Ohashi; Takashi Ota (Scientific Reports)
Abstract Despite much effort, the molecular mechanisms of retinal ganglion cell (RGC) death remain unclear. To identify common cell death-promoting machinery in the mechanically and chemically injured retina, we profiled temporal gene expression patterns and studied their functional roles in the rodent retina. In response to axotomy and intravitreal NMDA injection, 868 genes were commonly differentially expressed compared with those in normal retinas. K-means clustering assigned those common genes to 5 clusters on the basis of their temporal expression patterns, i.e., early, intermediate and late upregulated gene clusters, and early and late downregulated clusters. Most of the common genes and their assigned canonical pathways and molecular functions in each cluster were shared between axotomy and NMDA, indicating that their temporal expression profiles and functional roles are similar. Some of the common genes, including protein tyrosine phosphatases, formed specific molecular networks. Studies using chemical activators/inhibitors and knockout mice have demonstrated that protein tyrosine phosphatase 1/2 and interleukin-1 beta are detrimental to cell survival, whereas endothelin 2, the proteasome and galanin are neuroprotective. Thus, our integrated time-resolved expression profiling of common genes with bioinformatics and functional validation can help us to better understand the precise molecular mechanisms of RGC survival and death.